Kadar leptin saliva dan kejadian karies gigi anak obesitas (Salivary leptin levels and caries incidence in obese children) - Elfrida Atzmaryanni; Mochamad Fahlevi Rizal (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Children with obesity have a lower incidence of caries. Salivary leptin levels of obese children is higher than normal children. Leptin is protein hormone, contained in saliva. Salivary proteins maintain the balance of the ecosystem in the mouth. Purpose: The article was aimed to study the correlation of salivary leptin levels with caries incidence in obese children. Review: Mouth is reflection of the health status and so many changes occur as a weight gain. Child with obesity has a low incidence of caries than normal. This condition is associated with changes in oral cavity, especially the increase in salivary leptin. Caries is a disease of hard tissues cause by the activty of microorganisms, especially Streptococcus mutans. Salivary proteins maintain the balance of the ecosystem in the mouth. Leptin is a protein saliva, produced predominantly in adipose tissue and conduct active transport to saliva. Salivary leptin works in two ways: as an antimicrobial which prevents the attachment of bacteria on tooth surface or by inducing cytokine that affect the immune system in oral cavity. Conclusion: Salivary leptin is higher in obese children than in normal children. The low incidence of caries on obesity is associated with salivary leptin. Alteration in salivary composition and flow rate also decreased caries in obesity.Latar belakang: Anak yang mengalami obesitas memiliki insiden karies yang rendah. Kadar leptin saliva anak obesitas lebih tinggi dari anak normal. Leptin merupakan salah satu protein hormon yang terdapat di saliva. Protein saliva berfungsi untuk menjaga keseimbangan ekosistem di mulut. Tujuan: Artikel ini bertujuan mempelajari hubungan antara kadar leptin di dalam saliva dengan kejadian karies anak obesitas. Tinjauan pustaka: Rongga mulut merupakan cerminan dari status kesehatan dan banyak perubahan yang terjadi seiring peningkatan berat badan seseorang. Anak Obesitas memiliki insiden karies yang rendah jika dibandingkan anak normal. Kondisi ini berhubungan dengan perubahan keadaan rongga mulut terutama peningkatan kadar Leptin di saliva. Karies adalah penyakit jaringan keras yang disebabkan oleh aktivitas dari mikroorganisme, terutama Streptococcus mutans. Protein di saliva berfungsi menjaga ekosistem rongga mulut. Leptin merupakan protein saliva, leptin terutama di sintesis pada sel adiposa dan melakukan transport aktif sehingga dapat ditemukan di saliva. Leptin di saliva bekerja dengan dua cara yaitu sebagai antimikroba yang mencegah perlekatan bakteri di permukaan gigi atau dengan cara menginduksi sitokin yang mempengaruhi sistem imun dalam rongga mulut. Simpulan: Kadar leptin dalam saliva anak obesitas lebih tinggi dibanding anak normal. Rendahnya insiden karies anak obesitas berhubungan dengan kadar leptin di dalam saliva anak obesitas yang lebih tinggi dibandingkan anak normal. Perubahan komposisi saliva dan laju alir saliva pada anak obesitas juga menyebabkan rendahnya insiden karies dibandingkan dengan anak normal.